Digital Literacy and Teaching Creativity of Educators in Learning Activities: A Survey Method Review - Akib, Tasrif; Wajdi, Muhammad; Natsir, M; Hasan, Edi; Abidin, Abidin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This study aims to determine the relationship between educators' digital literacy skills and the creativity of teaching educators at state vocational high schools in Gowa Regency. This study applies a survey method that is correlational with a quantitative approach. The population in the study were educators with the status of civil servants in 5 state vocational high schools in Gowa Regency and as many as 70 educators who were sampled through the proportional random sampling technique in each population unit to obtain research data. This research used a Likeart scale questionnaire that has been validated and meets the reliability requirements. The data analysis technique to achieve the research objectives uses inferential statistics, namely simple correlation analysis. The results of the study reveal that, based on the Pearson correlation value obtained from a simple correlation analysis of 0.731 with a positive direction and sig.p 0.00 < (0.05) which gives an understanding that there is a significant relationship between educators' digital literacy skills and educators' teaching creativity at State Vocational High School in Gowa district, and obtained a coefficient of determination of 53%, which means that 53% of the total variance of the values ​​of educators' teaching creativity can be explained by the values ​​of educators' digital literacy skills.